Exploiting Phase-Change Memory in Cooperative Caches - Ramos, Luiz; Bianchini, Ricardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
Modern servers require large main memories, which so far have been enabled by improvements in DRAM density. However, the scalability of DRAM is approaching its limit, so Phase-Change Memory (PCM) is being considered as an alternative technology. PCM is denser, more scalable, and consumes lower idle power than DRAM, while exhibiting byte-address ability and access times in the nanosecond range. Unfortunately, PCM is also slower than DRAM and has limited endurance. These characteristics prompted the study of hybrid memory systems, combining a small amount of DRAM and a large amount of PCM. In this paper, we leverage hybrid memories to improve the performance of cooperative memory caches in server clusters. Our approach entails a novel policy that exploits popularity information in placing objects across servers and memory technologies. Our results show that (1) DRAM-only and PCM-only memory systems do not perform well in all cases, and (2) when managed properly, hybrid memories always exhibit the best or close-to-best performance, with significant gains in many cases, without increasing energy consumption.